2002
DOI: 10.1002/app.10402
|View full text |Cite
|
Sign up to set email alerts
|

Colon‐specific oral delivery of vitamin B2 from poly(acrylamide‐co‐maleic acid) hydrogels: An in vitro study

Abstract: Hydrogels, composed of poly(acrylamide-co-maleic acid) were synthesized and the release of vitamin B 2 from these gels was studied as a function of the pH of the external media, the initial amount of the drug loaded, and the crosslinking ratio in the polymer matrix. The gels containing 3.8 mg of the drug per gram gel exhibit almost zero-order release behavior in the external media of pH 7.4 over the time interval of more than their half-life period (t 1/2 ). The amount of the drug loaded into the hydrogel also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…This is a common phenomenon and has been reported in a number of studies. 26 Fabrication and characterization of the hydrogelsilver-nanoparticle composites…”
Section: Resultsmentioning
confidence: 99%
“…This is a common phenomenon and has been reported in a number of studies. 26 Fabrication and characterization of the hydrogelsilver-nanoparticle composites…”
Section: Resultsmentioning
confidence: 99%
“…We also previously reported such zeroorder release from a loosely crosslinked matrix. 4,12 To sum up, it can be concluded that the chemically treated hard gelatin capsules (0.53% formaldehyde solution; treatment time 45 s) containing riboflavinloaded poly(N-viny1-2-pyrrolidone)-polyacrylamide cylindrical gel with crosslinking ratio 0.3 (in mol %) may prove to be an effective device for causing the desired delay in release of drug for colon-targeted delivery of protein and peptide drugs.…”
Section: Kinetics Of Drug Releasementioning
confidence: 99%
“…In our laboratory, we have synthesized a number of pH‐sensitive hydrogels and studied their drug‐release behavior 2–5. These devices are supposed to function on the generally accepted view that the pH of the human gastrointestinal tract increases progressively from the stomach (pH 2–3), to the small intestine (pH 6.5–7.0), to the colon (7.0–8.0) 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic polymers based on polyacrylamide (PAAm) have already been used as pH‐sensitive drug delivery systems . The polymers based on PAAm that have been copolymerized with a carboxylic acid monomer, such as maleic acid (MA) containing ionizable carboxylic groups, are anionic and pH sensitive .…”
Section: Introductionmentioning
confidence: 99%